KEPALA MADRASAH SEBAGAI PEMIMPIN (LEADER) PENDIDIKAN - Ruma Mubarak (JANACITTA, 2022)
AbstractÂ Leadership is the ability to exert a constructive influence on others to make cooperative efforts to achieve planned goals. As a madrasah education leader, a madrasah head organizes the madrasa and the personnel who work in it into an efficient, democratic, and institutional cooperative situation that depends on the expertise of the workers. Under his leadership, educational programs for students had to be planned, organized and organized.Â Keyword: Head of Madrasah, Education Leader